Functionalized Multi-Walled Carbon Nanotube–Based Aptasensors for Diclofenac Detection - Zou, Yi; Griveau, Sophie; Ringuedé, Armelle; Bedioui, Fethi; Richard, Cyrille; Slim, Cyrine (Frontiers in Chemistry, 2022)
Driven by the increasing concern about the risk of diclofenac (DCF) residues as water pollutants in the aqueous environment and the growing need for its trace determination, a simple but sensitive electrochemical aptasensor for the trace detection of DCF was developed. To construct the aptasensor, the amine-terminated DCF aptamer was covalently immobilized on the surface of the carboxyl-functionalized multi-walled carbon nanotubes (f-MWCNTs) modified glassy carbon electrode (GCE). The immobilization was achieved through EDC/NHS chemistry. The f-MWCNTs provide a reliable matrix for aptamer immobilization with high graft density, while the aptamer serve as biorecognition probe for DCF. The obtained aptasensor was incubated with DCF solutions at different concentrations and was then investigated by electrochemical impedance spectroscopy (EIS). It displays two linear ranges of concentration for DCF detection, from 250 fM to 1pM and from 1 pM to 500 nM with an extremely low detection limit of 162 fM. Also, the developed biosensor shows great reproducibility, acceptable stability and reliable selectivity. Therefore, it offers a simple but effective aptasensor construction strategy for trace detection of DCF and is anticipated to show great potential for environmental applications.